"FROM MECCA WITH SELFIE" PHENOMENA: DECONSTRUCTION OF HAJJ AND UMRAH IN DA'WAH MANAGEMENT - Rolando, Dede Mercy; Ningsih, Rahmah (Multazam : Jurnal Manajemen Haji dan Umrah, 2023)
Problems often color the implementation of Hajj and Umrah in Indonesia, one of the actual issues that hit the Hajj and Umrah activities today is the phenomenon of the Indonesian people who like to selfie in front of the Kaaba or during the process of other worship activities. This study aims to look at the Hajj and Umrah guidance management strategies in Indonesia in implementing the Hajj and Umrah guidance functions. The method used as a blade in this study is a qualitative type with a phenomenological approach. The results of this study indicate that in order to improve the quality of the congregation, a strategy is needed in the form of pre-departure guidance, during activities, and after worship activities. This strategy can provide awareness to prospective pilgrims in understanding the meaning of each process of Hajj and Umrah activities which are carried out with full faith, piety, and humility in order to arrive at the mabrur goals of Hajj and Umrah. One of them is to become hajj and umrah pilgrims who are mabrur and avoid hedonism, materialism, and consumerism.